Znaczenie banków w finansowaniu inwestycji rzeczowych w polskim sektorze przedsiębiorstw - Samborski, Adam (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2014)
Research issues include the physical investment financing in Polish nonfinancial corporations in 1995 to 2011. The purpose of this study is to identify the structure of physical investment financing in Polish non-financial corporations, and to define the role of bank financing. The data used in the estimation of physical investment financing structure in Polish non-financial corporations, were obtained from two accounts belonging to the accumulation accounts, i.e. the capital account and the financial account. The study used net sources of finance methodology initiated by Mayer [1988, 1990], Corbett and Jenkinson [1994, 1997]. It uses the flow of funds rather than stock data.